2018
DOI: 10.1007/s12282-018-0888-y
|View full text |Cite
|
Sign up to set email alerts
|

CD44v9 as a poor prognostic factor of triple-negative breast cancer treated with neoadjuvant chemotherapy

Abstract: High CD44v9 expression in pre-NAC samples was associated with poor prognosis in TNBC patients treated with NAC, especially for those in whom pCR was not achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Regarding to countries, 10 studies were conducted in Japan, [ 17 , 20 25 , 27 , 30 , 31 ] 2 studies in China, [ 26 , 29 ] 1 study in Austria, [ 18 ] 1 study in Korea, [ 19 ] and 1 study in India. [ 28 ] With respect to types of cancer, 11 types of cancer were investigated, including head and neck cancer, [ 17 ] multiple myeloma, [ 18 ] gastric cancer, [ 19 , 21 , 25 , 31 ] upper tract urothelial cancer, [ 20 ] hepatocellular carcinoma, [ 22 ] colorectal cancer, [ 23 ] bladder cancer, [ 24 ] pancreatic cancer, [ 26 ] gallbladder cancer, [ 27 ] breast cancer, [ 28 , 30 ] and laryngeal cancer. [ 29 ] Besides, 11 studies reported the clinical stage of patients, [ 17 , 19 , 20 , 22 , 23 , 25 , 26 , 28 31 ] while 4 studies did not report the information about the clinical stage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding to countries, 10 studies were conducted in Japan, [ 17 , 20 25 , 27 , 30 , 31 ] 2 studies in China, [ 26 , 29 ] 1 study in Austria, [ 18 ] 1 study in Korea, [ 19 ] and 1 study in India. [ 28 ] With respect to types of cancer, 11 types of cancer were investigated, including head and neck cancer, [ 17 ] multiple myeloma, [ 18 ] gastric cancer, [ 19 , 21 , 25 , 31 ] upper tract urothelial cancer, [ 20 ] hepatocellular carcinoma, [ 22 ] colorectal cancer, [ 23 ] bladder cancer, [ 24 ] pancreatic cancer, [ 26 ] gallbladder cancer, [ 27 ] breast cancer, [ 28 , 30 ] and laryngeal cancer. [ 29 ] Besides, 11 studies reported the clinical stage of patients, [ 17 , 19 , 20 , 22 , 23 , 25 , 26 , 28 31 ] while 4 studies did not report the information about the clinical stage.…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 , 26 28 ] As for clinical outcomes, 12 studies reported clinicopathological parameters, [ 18 26 , 28 , 29 , 31 ] 6 studies reported OS, [ 18 , 19 , 22 , 23 , 26 , 27 ] 2 studies reported DSS, [ 17 , 25 ] 2 studies reported CSS, [ 20 , 24 ] 4 studies reported RFS, [ 20 22 , 31 ] 1 study reported PFS [ 24 ] and 1 study reported DMFS. [ 30 ] Additionally, regarding to the analysis model of survival, 7 studies used the multivariate analysis model [ 17 , 18 , 20 , 22 , 23 , 25 , 26 ] and 3 studies used the univariate analysis model. [ 19 , 24 , 27 ] NOS score was ≥6 in all studies, which suggested that all studies were with relatively high quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CD44v9 + group had a poor prognosis for hepatocellular carcinoma, breast cancer, plasmacytoma, gastric cancer, bladder cancer, gallbladder cancer and ICC (15,21,(30)(31)(32)(33). There was, however, no signi cant difference in the PFS and OS between the CD44v9 + and CD44v9 − groups by the Kaplan-Meier method (log-rank test) and Cox proportional hazards model in the present study (Tables 3 & 4, Fig.…”
Section: Discussionmentioning
confidence: 44%